(untitled) (World Bulletin of Social Sciences, 2024)
This article discusses the policy and strategies of the United States towards the Central Asian countries (Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan) and how recent developments in Afghanistan have impacted this policy. The US aims to promote stability, prosperity, and democratic institutions in Central Asia. It also seeks to counter terrorism, secure energy supplies, and expand economic opportunities. Moreover, the Taliban takeover of Afghanistan in 2021 has created new challenges and opportunities for US policy in Central Asia. The US is concerned about the potential resurgence of terrorist groups and the rollback of human rights gains in Afghanistan. However, the Taliban’s control of Afghanistan also presents an opportunity for regional stability if they cooperate with the international community. The article concludes by suggesting that the U.S. policy towards Afghanistan has a two-sided impact on security in Central Asia